Pelvic floor muscle training associated with the photobiomodulation therapy for women affected by the genitourinary syndrome of menopause: a study protocol - Lívia Oliveira Bezerra; Maria Letícia Araújo Silva de Carvalho; Edson Silva-Filho; Maria Clara Eugênia de Oliveira; Palloma Rodrigues de Andrade; Maria Thereza Albuquerque Barbosa Cabral Micussi (PeerJ)
Background Frequently, the women affected by the genitourinary syndrome of menopause experience genitourinary dysfunctions that profoundly influence their overall health. Even though the symptoms do not jeopardize the women’s lives, the urinary and sexual dysfunctions significantly impact their quality of life. Isolated treatments focused on the main causes of the dysfunctions, such as pelvic floor muscle training (PFMT) and photobiomodulation have shown significant improvements in genitourinary dysfunctions. So, the association of PFMT with photobiomodulation may generate additional effects in the genitourinary area. This study aims to create a PFMT protocol isolated and associated with photobiomodulation therapy in women affected by the genitourinary syndrome of menopause. Methods It is a randomized, controlled, double-blind clinical trial protocol study that will include women experiencing genitourinary symptoms related to menopause, sexually active, never practiced pelvic floor muscle exercise or photobiomodulation treatment, and do not use hormone replacement therapy for at least 3 months. The randomization will allocate the women to three groups: PFMT group, PFMT associated with active intracavitary photobiomodulation group, and PFMT associated with sham intracavitary photobiomodulation group. A total of 16 sessions will be conducted twice a week. The assessments will occur before interventions, after the sixteenth session, and 1 month after the sixteenth session (follow-up). The evaluation will include the pelvic floor muscle vaginal manometry as the primary outcome. Also, the international consultation on incontinence questionnaire—short form, the female sexual function index, the Utian Quality of Life scale, the patient global impression of improvement, the modified Oxford scale, and the vaginal health index will be the secondary outcomes. Discussion Despite there are gold standard treatments such as PFMT, to alleviate genitourinary symptoms, interventions mirroring clinical practice are needed. This study protocol might show a groundbreaking and viable method to potentiate the effects of a gold-standard treatment associated with photobiomodulation. Conclusion We expect this protocol to demonstrate that the use of PFMT and photobiomodulation strategies is feasible and able to potentiate the recovery of women affected by the genitourinary syndrome of menopause. The Ethics Committee of the Federal University of Rio Grande do Norte approved the study (n° 6.038.283), and the clinical trials platform registered the protocol (n° RBR-5r7zrs2).